KOMPONEN CLIENT SERVER THREE TIER PADA PEMBANGUNAN WEB SERVICE ANGGOTA PERPUSTAKAAN UNIVERSITAS MUHAMMADIYAH BENGKULU - Cahyo Prihantoro; Harry Witriyono (Universitas Muhammadiyah Semarang, 2018)
The three-tier client server component thin client thick server is a further development than previously using two tiers. The use of this model is expected that the application no longer needs to be installed on each client but only on the server. Besides that with this model the application that is server side can be accessed by each client in various types of operating systems and hardware used. The workload of library transaction services can spread and no longer accumulate on one working terminal, but it can be spread to other terminals, that is the benefit of this technology. Although the service workload is spread, but the data and information needed is integrated on the server, so that data synchronization in the formation of information becomes more accurate, fast and efficient. An integrated information system between Academic Information Systems and Library Information Systems makes data more accurate and well distributed. The basic components used are servers, routers, and program codes for web services (JSON, XML). Three tiers have a database layer on server 1, the application layer is on server 2, and layer 3 is on the user's side. Keywords: client server, information system, library information system, academic information system, integrated system.